Creating Learning: A Critical Program Planning Praxis For Collaborative Knowledge Construction and Social Change - Colleen Aalsburg Wiessner (Adult Education Research Conference, 2009)
Positing an alternate program planning perspective, this paper explores the possibility of viewing planning as a critical praxis. It blends theory and practice in development, content, and research approach; explores meanings and functions of praxis as a rationale for this perspective; and outlines purposes, principles and practices of the approach.